Konstruktion av kullagertestrigg - Mattsson, Per (2011)
Rolling element bearings are vital components in almost every machine or application with moving or rotating parts. Therefore it is of great importance to fully understand the behaviour of the bearings. Today there are good ways to predict the expected service life of a rolling element bearing but there is no way to calculate the exact service life, and this can lead to serious and costly consequences in the event of a breakdown. This thesis work aims to build a test equipment in which it is possible to apply a load on the bearing and then measure the torque from the bearing and see how the torque will react near failure. Most interesting is the analysis of the bearing operating in low rpm when vibrations can be hard to use for evaluation of the condition of the bearing. The rig was designed at Luleå University of Technology and built in the workshop at the department, “Handverkstan”. The design aimed mostly on an as simple as possible design, where most parts could be manufactured by hand. Changes of the bearing between tests should also be simple to perform. The performance of the rig and the outcome of data are within requirements of specification. The torque can easily be measured over time for a rpm up to 2000. The electric motor does not allow testing in lower rpm since the torque is too low, so a new motor is required for tests in low rpm. Validerat; 20111117 (anonymous)